2014
DOI: 10.1016/j.bjan.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparação dos efeitos de sulfato de magnésio e da dexmedetomidina sobre a qualidade da visibilidade em cirurgia endoscópica sinusal: estudo clínico randomizado

Abstract: Due to its reduction of bleeding and heart rate in endoscopic sinus surgery and its positive impacts on the duration of surgery, we consider dexmedetomidine to be a good alternative to magnesium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
1
10
0
4
Order By: Relevance
“…And then 4 studies were excluded by full-text review for they were performed in pediatric patients. At last, 10 RCTs were enrolled in further meta-analysis [14][15][16][17][18][19][20][21][22][23]. The identification procedure of these eligible articles is described in Fig 1. The enrolled studies were published from 2011 to 2018, and all of them were published in English.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…And then 4 studies were excluded by full-text review for they were performed in pediatric patients. At last, 10 RCTs were enrolled in further meta-analysis [14][15][16][17][18][19][20][21][22][23]. The identification procedure of these eligible articles is described in Fig 1. The enrolled studies were published from 2011 to 2018, and all of them were published in English.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…A total of 663 patients were randomized to receive two drugs. In 10 included RCTs, 5 were researches about head and neck surgery [14][15][16][17][18], 3 were researches about spinal surgery [19][20][21], and the rest two trials were researches about pituitary adenoma surgery [22] and laparoscopic colorectal resection surgery [23]. All enrolled studies reported the hemodynamic parameters (MAP, HR), and 6 studies reported the evaluation of surgical field bleeding by using 6-point scale [14][15][16][17][18]22].…”
Section: Basic Characteristics Of Enrolled Studiesmentioning
confidence: 99%
See 3 more Smart Citations